Transition-metal-free [3 + 3] annulation of indol-2-ylmethyl carbanions to nitroarenes. A novel synthesis of indolo[3,2-b]quinolines (quindolines) - Nowacki, Michał; Wojciechowski, Krzysztof (Beilstein Journal of Organic Chemistry, 2018)
Indol-2-ylmethyl carbanions stabilized by alkoxycarbonyl, cyano or benzenesulfonyl groups react with nitroarenes to form σH-adducts, which in the presence of base (triethylamine or DBU) and trimethylchlorosilane transform into indolo[3,2-b]quinoline derivatives in moderate to good yields.
Keywords: carbanions; cyclization; heterocycles; nitroarenes; nucleophilic substitution; silylation